PERAN PERGURUAN TINGGI AGAMA DALAM MEMBANGUN PERDAMAIAN BERBASIS PANCASILA DI JAKARTA - Sofyan, Ahmad; Misriandi, Misriandi; Lesmana, Johan Aristya (Ibn Khaldun University, Bogor, 2022)
The role of Islamic Religion College in developing the peace is evidenced by the effort to implement The Five Pilar (Pancasila) Education as the foundation to grow the nationalist and citizenship awareness of Religious people. In the contestation of Jakarta Governor Election, 4 Islamic Religion Colleges contributed in keeping the peace and conduciveness. The role of State Islamic University (UIN) Syarif Hidayatullah Jakarta in the implementation of The Five Pilar (Pancasila) Education as the effort to develop the peace through curriculum approach integrated in lecturing class is always being integrated by the Islamic-Indonesian values as the academic wisdom and the understanding of wasathon (Moderate) Islamic thought in the moderation of religiuos in order to avoid either the extremism understanding or liberalism as the religious wisdom. Regarding to the role of Muhammadiyah University Jakarta, it empashizes the Muhammadiyah social values to be the spirit in conducting the education. This is written in Muhamamdiyah College Duty (Darma Perguruan Tinggi Muhammadiyah), namely: Al-Islam, Muhammadiyah values, education, research and dedication to the society as academic wisdom. Afterwards, the principle of peace and advanced Islam as religious wisdom. Then, Islam University Jakarta plays a role in conducting the peace through academic and non-academic activities integrated by Islamic values in every single of it. The Islamic Studies (dirasah Islamiyah) in Islam University Jakarta is becoming the main subject in all majors for 4 semesters. This is also becoming both the academic wisdom and the religious one performed by the college. The other one is Nahdhotul Ulama University Jakarta, it has the mechanism of conflict resolution as the effort to develop the peace in Jakarta with Islamic-Indonesian values. It aims to develop its students through Pesantren model in order to improve their academic and to apply religious wisdom through Islam Archipelago (Nusantara) as the special characteristic in growing the awareness of nationalism and religiousness. This research employs descriptive qualitative method and in order to provide the balance of the data, the researcher undertakes interview with The Commission of Fatwa Majelis Ulama Indonesia (MUI) and The commission member II of The Republic Indonesia Parliament (DPR RI). The factors which influence the implementation of The five pilar (Pancasila) education in order to develop the peace after Jakarta governor election, namely: the endurance of citizen, detection and early response system to the conflict in the form of communication among the society, and the empowerment of citizen as the effort to cultivate the citizen’s awareness regarding the political issue.